NEBULAR: A Simple Synthesis Code for the Hydrogen and Helium Nebular Spectrum. (29th September 2016) - Schirmer, Mischa
Abstract: NEBULAR is a lightweight code to synthesize the spectrum of an ideal, mixed hydrogen and helium gas in ionization equilibrium, over a useful range of densities, temperatures and wavelengths. Free–free, free-bound and two-photon continua are included as well as parts of the Hi, Hei and Heii line series.NEBULAR interpolates over publicly available data tables; it can be used to easily extract information from these tables without prior knowledge about their data structure. The resulting spectra can be used to e.g., determine equivalent line widths, constrain the contribution of the nebular continuum to a bandpass, and for educational purposes.NEBULAR can resample the spectrum on a user-defined wavelength grid for direct comparison with an observed spectrum; however, it can not be used to fit an observed spectrum.